2009
DOI: 10.1111/j.1471-4159.2009.06402.x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of AD‐like neuropathology by harnessing peripheral immune cells: local elevation of IL‐10 and MMP‐9

Abstract: Immunization with an altered myelin‐derived peptide (MOG45D) improves recovery from acute CNS insults, partially via recruitment of monocyte‐derived macrophages that locally display a regulatory activity. Here, we investigated the local alterations in the cellular and molecular immunological milieu associated with attenuation of Alzheimer’s disease‐like pathology following immunotherapy. We found that immunization of amyloid precursor protein/presenilin 1 double‐transgenic mice with MOG45D peptide, loaded on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
117
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 101 publications
(125 citation statements)
references
References 107 publications
7
117
1
Order By: Relevance
“…Such cells are often considered infiltrating myeloid cells (36). Our data showed fewer such cells in the AD + ACE 10/10 mice, but these data did not reach statistical significance.…”
Section: Figurecontrasting
confidence: 74%
See 4 more Smart Citations
“…Such cells are often considered infiltrating myeloid cells (36). Our data showed fewer such cells in the AD + ACE 10/10 mice, but these data did not reach statistical significance.…”
Section: Figurecontrasting
confidence: 74%
“…Further, we found that following immunization, increased peripheral monocyte-derived macrophages homed to Aβ plaques and facilitated their clearance (31,36). These and other studies suggest that BM-derived macrophages are more efficient than microglia in restricting Aβ plaques in mouse models of AD (29-31, 34, 36-41).…”
Section: Introductionsupporting
confidence: 75%
See 3 more Smart Citations